Firm‐Wide Incentives and Mutual Monitoring at Continental Airlines - Knez, Marc; Simester, Duncan (Journal of Labor Economics, 2001)
In February 1995 Continental Airlines introduced an incentive scheme that promised monthly bonuses to all 35,000 hourly employees if the company achieved a firm-wide performance goal. Conventional wisdom suggests that free riding will render such schemes ineffective. We present evidence indicating that the incentive scheme raised employee performance despite the apparent threat of free riding. To explain why the scheme may have been effective we argue that the organization of employees into autonomous work groups enabled Continental to induce mutual monitoring among employees within each work group. Copyright 2001 by University of Chicago Press.